The peculiarities of intellectual activity of junior school age children - Butkienė, G.; Jagutytė, R.; Grakauskaitė, D. (Psichologija, 1984)
The present paper gives an account of the peculiarities of first-formers’ and fourth-formers’ intellectual activity as a significant unit of creativity and its relation to their general mental abilities, learning proficiency, and the inclination to play chess. Intellectual activity and need for cognition were investigated by the so-called “creative field” methods, recommended by D. B. Bogoyavlenskaya. General mental abilities of the pupils were defined by D. Wechsler and I. Raven’s test. The analysis of the research data has revealed that most pupils belong to the lower and medium levels of intellectual activity. It proves that so far neither at home nor at school there are no adequate conditions for the development of pupils’ creativity. The results of the analysis of their need for cognition have confirmed the same. They are closely related to the data of investigation of intellectual activity, obtained by the “creative field” methods (p 0,001). It has been testified that there is statistically significant, but versatile dependence between intellectual activity and general mental abilities (p 0,01). We did not establish any significant dependence between intellectual initiative, fixed by the “creative field” methods, and general mental abilities. Meanwhile a more firm connection was found between the expression of intellectual activity in everyday life of the pupils (the need for cognition), general mental abilities and their learning proficiency (p 0,01). Both the indices of intellectual activity are more developed in most children permanently engaged in chess-playing. We consider that chess-playing gives great possibilities for the development of intellectual initiative and general intellectual abilities of pupils.